Pengaruh electronic word of mouth, gaya hidup dan kepercayaan terhadap keputusan pembeli online melalui shopee - Tammu, Rahma Gusmawati; Palimbong, Stefani Marina (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this study was to identify the influence of Electronic Word of Mouth, lifestyle, and trust on online purchasing decisions through shopee on students of the Faculty of Economics, UKI Toraja Management Study Program. The type of research conducted is descriptive quantitative. The data analysis technique used multiple linear regression. The results showed that there was no influence of electronic word of mouth on purchasing decisions. There is no influence of lifestyle on purchasing decisions. There is an influence of trust on online purchasing decisions. Electronic Word of Mouth, lifestyle, and trust have a significant simultaneous effect on purchasing decisions on the Shopee application through shopee for students of the Faculty of Economics, UKI Toraja Management Study Program.